Storytelling Marketing Design of Wanaland Coffee Roastery To Improve Brand Awareness - Mahendra, Muhammad Chosasih; Retnaningsih; Rahmana, Adhitya (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The trend of coffee consumption in Indonesia encourages many business players in the coffee industry. Storytelling marketing is one of the tools that can be used to build brand awareness and, in the long run, will encourage consumer buying interest. Purpose: This research aims to identify business activities and brand awareness levels and provide a storytelling marketing design for Wanaland Coffee Roastery.Design/methodology/approach: Data was collected through in-depth interviews, online surveys, and literature studies. Quantitative data processing and descriptive statistics results are then analyzed using value chain analysis tools, brand awareness pyramids, and marketing storytelling.Findings/Result: The results of this study are in business activities, Wanaland Coffee Roastery sells coffee in the form of beans offline and online. The promotional media used are Facebook, WhatsApp, Instagram, and word-of-mouth. Brand awareness that is derived from promotional activities that have been carried out is still minimal, so storytelling marketing is used to increase brand awareness. Storytelling design was organized into three scenarios by utilizing five digital communication channels: website, social media, Google My Business, e-commerce, and SEO/SEM.Conclusion: Based on the research results, consumer brand awareness is still low. Therefore, the marketing storytelling design in this study is needed to increase brand awareness.Originality/value (State of the art): Research conducted at Wanaland Coffee Roastery using a storytelling marketing strategy is the novelty of this research because no similar research has been found. Keywords: brand awareness, coffee business, digital marketing, storytelling, value chain analysis